Dinamika Inovasi Organisasi dalam Menghadapi Disrupsi AI dan Transformasi Digital untuk Mempertahankan Keunggulan Kompetitif pada Perusahaan Teknologi di Indonesia - Maulana, Panca; Riyadi, Selamet; Lestari, Setyani Dwi; Safitra, Ravindra; Nugroho, Heru (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Facing the wave of disruption caused by artificial intelligence (AI) and digital transformation, technology companies in Indonesia are required to develop organizational innovations that not only focus on technology but also encompass culture, leadership, and cross-functional collaboration. This research aims to analyze how technology companies maintain their competitive advantage through the integration of innovations across various sectors. Using a mixed-method approach, data was collected through in-depth interviews with industry practitioners and quantitative surveys of leading technology companies. The study results show that companies that are proactive in innovation, adopt AI, and foster a collaborative and experimental culture are able to improve operational efficiency, enhance customer experience, and strengthen market position. The main challenges include cultural resistance, resource limitations, and issues of data security and regulation. However, companies that prioritize visionary leadership and data-driven strategies are proven to be more adaptable to market dynamics. These findings emphasize the importance of a holistic innovation approach to maintain sustainable competitive advantage. This study is expected to provide practical contributions to policymakers and industry players in formulating innovation strategies in the digital era.